GP perceptions of the adequacy of community-based care for patients with advanced heart failure in a UK region (NI): a qualitative study. Issue 1 (5th April 2018) - Chen, Jingwen Jessica; Gamble, Kathryn; Graham-Wisener, Lisa; McGlade, Kieran; Doherty, Jennifer; Donnelly, Patrick; Stone, Carol A
Abstract : Objective: To assess the adequacy of community-based services available in Northern Ireland (NI) and to meet the multidimensional needs of patients living with New York Heart Association Stage III and IV heart failure (HF), as experienced and perceived by general practitioners (GP). Methods: Semistructured interviews were conducted with GPs recruited via the University Department of General Practice and Northern Ireland Medical and Dental Agency. Interviews were transcribed, independently coded and analysed using a six-step thematic analysis approach. Results: Twenty semistructured interviews were conducted. GPs reported managing patients in a 'reactive rather than proactive' way, responding only to acute medical needs, with hospital admission the default option due to lack of community-based expertise and services. Care provided by HF specialists was highly regarded but 'access and coordination' were lacking, related to inequity of access to Heart Failure Nursing Teams, lack of access to specialist advice and inadequate handover of information to GPs. Conversations regarding current and future care needs and preferences were important, but GPs described 'neglecting conversations with the patient', due to time constraints, prognostic uncertainty and fear of causing distress. They expressed the view that 'specialist palliative care (SPC) is only a credible option in end stages' related to limited understanding of the scope of SPC, a perception that timing of referral must depend on prognosis and concern that SPC services are cancer-focused. Conclusions: Despite the extensive body of research which evidences the unmet multidimensional needs of patients with advanced HF, and more recent evidence for the effectiveness of integrated SPC in improving quality of life for patients with HF, health and social care services within NI have not adapted to assess and meet these needs.